Social Media Influencer’s Credibility and Consumer Purchasing Behaviour in Benin City, Nigeria - Omoniyi, Imouokhome Ebun; Osasere, Iyamu Gloria (NIU Journal of Management Sciences, 2026)
This study examined the influence of influencers credibility on consumer purchase behaviour in Benin City, Nigeria. It specifically, explored how influencers’ credibility (trustworthiness, expertise, attractiveness) influences the purchase decisions of social media users. Quantitative survey design was used for the study, and data were collected from 385 respondents using structured questionnaires. Inferential statistics analyses were carried out using regression analysis and the hypotheses were tested at 0.05 significant level. The findings revealed that trustworthiness, expertise, and attractiveness significantly influence consumer purchase decisions, with trustworthiness having the strongest effect. The study concludes that influencers credibility significantly reform consumer purchase patterns through personal attributes. It recommends that brands should always engage credible and authentic influencers to build trust and foster long-term consumer loyalty. Keywords: Attractiveness; Consumer Purchase Decisions; Expertise; Influencer Credibility; Trustworthiness.